Strategies for Revitalizing Tri Tangtu Local Wisdom Among College Students - Runik Machfiroh; Ida Rohayani; Dicky Hidayat (STAI Hubbulwathan Duri, 2024)
The challenge of integrating local wisdom values into the education of the younger generation, especially in the era of digital advancement marked by transitions from 4.0 to 5.0, is primarily due to a lack of awareness, educational curriculum gaps, and generational differences in understanding these values. This research focuses on the Tri Tangtu concept—a key element of West Java's traditional wisdom—emphasizing its significance in maintaining societal balance and harmony between individuals and their environment. The aim is to analyze Tri Tangtu comprehensively and develop strategies to rekindle students' interest in preserving and understanding this cultural legacy. Adopting a qualitative research approach, this study delves into the complexities of rejuvenating Tri Tangtu for student engagement, with data collection conducted through purposive sampling interviews, centering on students from Telkom University in Bandung, Indonesia. Results indicate a decline in students' engagement with traditional cultural values, often perceived as restrictive or superstitious. Notably, this research innovates by strategizing the revival of Tri Tangtu through new media platforms. It concludes that integrating local wisdom values into the curriculum, supported by social programs, community engagement, and technological interventions, is crucial for fostering students' cultural identity.